Anthropological Theory and Government Policy in Australia's Northern Territory: The Hegemony of the "Mainstream". Issue 2 (17th May 2013) - Morphy, Frances; Morphy, Howard
ABSTRACT In this article, we set up a dialogue between two theoretical frameworks for understanding the developing relationships between indigenous Australians and the encapsulating Australian society. We argue that the concept of "the intercultural" de‐emphasizes the agency of Aboriginal people and the durability of their social relations and value orientations. We develop the concept of relative autonomy in apposition. Our primary focus is on the Yolngu people of eastern Arnhem Land and on the impact that recent Australian government policy—in particular the Northern Territory "Intervention"—has had on the relatively autonomous trajectory of their society. The view from relative autonomy enables an understanding of the history of Yolngu interaction with outsiders and Yolngu responses to government policy. We argue that unless relative autonomy is understood and taken into account, governments will fail to develop policies that engage Yolngu in the process of regional development.